Implementation of Stewardship and Contingency Theory in Islamic Cash Management - Bagas Pangestu Pribadi; Ngurah Ayu Dian Anggraeni; Sodikin Manaf (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research aims to explore the meaning of cash management in MSMEs in the midst of the dynamics of tax compliance and religiosity values. Using a hermeneutic phenomenological approach, this study constructs a cash management model that is rooted in the integration of Stewardship Theory (spiritual motivation) and Contingency Theory (situational adaptation). The results of the study show that the integration of the two theories gave birth to the practice of Islamic Cash Management which consists of five dimensions: (1) Prudential-based Cash Planning (Ihtiyath) and Wealth Guard (Hifz al-Mal); (2) Cash control that upholds the trust; (3) Cash & Liquidity Management to achieve benefits (Maslahah) and balance (Tawazun); (4) Transparent and fair ('Adl) Cash Conversion Cycle; and (5) Cash Reporting and Visibility as a form of transparency (Bayan) and self-evaluation (Muhasabah). These five dimensions collectively shape and direct three main cash flows: Cash Inflows as a survival strategy, Social Responsibility as wealth purification, and Cash Outflows as social capital investments. In conclusion, this model confirms that MSME resilience is built through a balance between business rationality and transcendental accountability.